2004
DOI: 10.1590/s0100-879x2004000600009
|View full text |Cite
|
Sign up to set email alerts
|

Can calories from ethanol contribute to body weight preservation by malnourished rats?

Abstract: Our objective was to compare the use of calories from ethanol by wellnourished and malnourished rats in terms of body weight. Female Wistar rats weighing 170-180 g at the beginning of the study were used. The animals were divided into two groups (N = 12 each): group W received water ad libitum and group E an ethanol solution ad libitum as the only source of liquid throughout the experiment. The concentration of ethanol was increased weekly from 0 to 5, 10, 20 and 40% (v/v). In the well-nourished phase (A), all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
3
10
0
5
Order By: Relevance
“…Ethanol at 5%v/v in drinking solution was beneficial to malnourished rats in all parameters evaluated in this study (body weight, biochemical parameters and liver histopathology). This is in accordance with Aguiar et al (2004), who reported that malnourished rats utilized ethanol calories for body weight maintenance up to ethanol concentrations in drinking water at 20%v/v. Malnutrition significantly increased ethanol consumption in g/kg body weight.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ethanol at 5%v/v in drinking solution was beneficial to malnourished rats in all parameters evaluated in this study (body weight, biochemical parameters and liver histopathology). This is in accordance with Aguiar et al (2004), who reported that malnourished rats utilized ethanol calories for body weight maintenance up to ethanol concentrations in drinking water at 20%v/v. Malnutrition significantly increased ethanol consumption in g/kg body weight.…”
Section: Discussionsupporting
confidence: 92%
“…Aguiar et al (2004) evaluated the threshold dose in which ethanol would be useful as an energy source to malnourished rats. Ethanol solutions at 5, 10 and 20% v/v decreased body weight loss in malnourished rats and did not change biochemical parameters (hematocrit, hemoglobin, total protein and albumin).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies show that the consumption of low to moderate doses of alcohol (up to 20% of total caloric intake) causes weight gain in malnourished rats, which suggests an effective utilization of alcohol energetic content. Eutrophic rats, however, lose weight when the energetic content of alcohol represents 10% or more of the total calorie intake [21,22].…”
Section: Alcohol and Malnutritionmentioning
confidence: 99%
“…O etanol fornece calorias em seu metabolismo (7,1 kcal/g), sendo uma fonte energética intermediária em relação às proteínas e aos carboidratos, que fornecem 4,0 kcal/g, e aos lipídios, que fornecem 9,0 kcal/g. O aproveitamento orgânico da energia fornecida pelas bebidas alcoólicas dependerá do estado nutricional, da frequência e do modo de consumo, podendo levar ao sobrepeso e à obesidade, em consumidores moderados, e à desnutrição entre os usuários crônicos 8,20,21 .…”
Section: Discussionunclassified
“…Por ser fonte de calorias desprovidas de vitaminas e minerais, o consumo crônico de etanol causa desnutrição específica, além de promover a diminuição do consumo de alimentos e prejudicar a absorção dos nutrientes 7 . Entretanto, estudos com animais indicam que o consumo de doses baixas a moderadas de álcool promovem o ganho de peso de ratos desnutridos, sugerindo o aproveitamento de sua energia 8,9 .…”
Section: Introductionunclassified